Aplicação do indicador de proximidade de áreas verdes urbanas na cidade de Jaboticabal - SP - Russo, Renato Anselmo (2005)
Several studies have been done with urban green areas used as indicators of the sustainability in the Environmental Planning of a city. The current study aimed to apply an indicator of sustainability to central green areas of Jaboticabal city (state of São Paulo) and to interpret its behavior. For this, a characterization of these green areas, which areas located in the urban perimeter of the city, was made citing its measures, type of use, conservation conditions, location and vegetation. The chosen indicator, which is the same to other identified experiences, was the Green Area Proximity Index (IPAV), considering 300 or 500 meter distances. The IPAV enables the adoption of a graphic instrument for its calculation and analysis. The developing of graphic instruments related to the chosen indicators increases the number of interpretations which can also be used for other studies. The result obtained with the used of IPAV has raised questions regarding its efficiency, when applied in isolation, because it can interfere in the value of other indicators. However the IPAV is a valuable tool to help in the distribution of the green areas inside the urban region. The main idea is that this study may contribute as a tool to the Environmental Planning of a city, along with Sustainable Urbanization, resulting in a better quality of life for people. This scientific contribution is intended to give support to pertinent actions to our reality without jeopardizing future situations.